Analisis Penggunaan Perangkat Internet of Things (IoT) pada Novel Hujan Karya Tere Liye - Khairil Hamdi; Abdul Khaliq; Eva Dwi Kurniawan (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This study aims to analyze the use of Internet of Things (IoT) technology in the novel "Hujan" by Tere Liye. This novel shows how the love story and life struggle of the main character, Lail, are connected to the development of IoT technology. This research aims to understand how IoT technology shapes the story from the aspect of the situation to the characteristics of the related IoT devices. Through the hermeneutic method, this research identifies the use of IoT in several contexts. The findings obtained in the novel are 1) Smart Buildings, 2) Smart Farming, 3) Smart Home, 4) Smart City, and 5) Smart Healthcare. The results show that IoT technology is a key element in achieving a more advanced and connected digital society, bringing positive impacts in daily life and providing smart solutions to various global challenges.